Composite diaphragm as well as preparation and application thereof in lithium ion battery

By using a composite structure of base film, ceramic coating and electrospinned organic polymer coating in the lithium-ion battery separator, the problems of poor thermal stability and low lyophilicity of traditional separators are solved, and efficient electrolyte wetting is achieved and safety performance improvement.

CN119419447AInactive Publication Date: 2025-02-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202510012980.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional lithium-ion battery separators have problems such as poor thermal stability, low lyophilicity, low conductivity, poor adhesion, and easy peeling of ceramic layers, resulting in battery safety hazards and cycle attenuation.

Method used

Using a composite separator composed of a base film, a ceramic coating and an organic polymer coating, the ceramic coating enhances heat resistance and electrolyte wetting through an aqueous coating process, and the organic polymer coating prepared by electrospinning forms spherical beads. Structure, improve wettability and adhesion.

Benefits of technology

The composite separator has achieved high thermal stability, low moisture content, excellent electrolyte wetting and liquid retention rate, which significantly improves the safety performance and stability of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419447A_ABST
    Figure CN119419447A_ABST
Patent Text Reader

Abstract

The invention discloses a composite diaphragm as well as preparation and application thereof in a lithium ion battery, and belongs to the technical field of lithium ion battery materials. The composite diaphragm comprises a base material, at least one ceramic coating and at least one organic polymer coating, wherein the surface of the base material is coated with the at least one ceramic coating and the at least one organic polymer coating. The thickness of the ceramic coating is 1-3 m, and the thickness of the organic polymer coating is 0.3-5 m. And the ceramic coating is prepared by adopting a water-based coating process, so that the heat resistance and electrolyte wettability of the diaphragm can be improved. The organic polymer coating is prepared in an electrostatic spinning mode, and a spherical bead structure is formed by adjusting spinning parameters. Due to the fact that a large number of bead structures are contained, the prepared composite diaphragm shows stable super-hydrophobic performance. And the organic polymer has extremely high heat resistance and cohesiveness to a pole piece, and the diaphragm is endowed with extremely high porosity by the electrostatic spinning preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite diaphragm and its preparation and application in lithium ion batteries. Background Art

[0002] Lithium-ion batteries are widely used as power sources for various mobile devices due to their high energy density, high operating voltage, no memory effect and long cycle life. From 2017 to 2022, global lithium battery shipments increased from 160 GWh to 1080 GWh, and China's share increased from 33% to 83%. It is expected that global lithium battery shipments will reach 2347 GWh in 2025, of which China will account for about 89%. Correspondingly, global lithium battery separator shipments have increased year by year. It is expected that by 2025, global separator usage will reach 36.5 billion square meters, which has a huge market demand.

[0003] Traditional polyolefin diaphragms have large thermal shrinkage, which leads to battery short circuits and frequent lithium battery safety accidents. In order to improve the thermal stability of the diaphragm, ceramic coating diaphragm technology is usually used to coat a ceramic layer on the surface of the polyolefin diaphragm to improve the thermal stability of the diaphragm. However, ceramic diaphragms have problems such as poor lyophilicity, low ionic conductivity, poor adhesion to the pole piece, easy detachment of the ceramic layer, and easy pore clogging by ceramic particles. Moreover, ceramic particles have strong water absorption, which can easily cause quality risks such as rapid battery cycle decay. In addition, the high specific gravity of ceramics is not conducive to the lightweighting of large power batteries. Summary of the invention

[0004] In view of the deficiencies in the prior art, one of the objects of the present invention is to provide a composite diaphragm having good thermal stability, low moisture content, high lyophilicity and liquid retention rate, thin thickness and low resistance.

[0005] The second object of the present invention is to provide a method for preparing a composite diaphragm, which is easy to control and has high production efficiency, and can produce a diaphragm material with high quality, reducing battery quality risks and effectively improving battery safety.

[0006] The third object of the present invention is to provide application of the composite diaphragm in lithium ion batteries.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solution: a composite diaphragm, consisting of a base membrane and one or more ceramic coatings attached to one or both sides of the base membrane, and one or more organic polymer coatings attached to the surface of the ceramic coating.

[0008] The ceramic coating is obtained by coating and drying a ceramic coating solution. The organic polymer coating is obtained by spinning, hot pressing and drying an organic polymer spinning solution. The thickness of the ceramic coating is 1-3µm, preferably 1.5-2.5µm, and the thickness of the organic polymer coating is 0.3-5µm, preferably 0.8-3µm.

[0009] The organic polymer includes one or more of aramid, polyimide, polyaryletherketone, polyacrylonitrile, polyvinylidene fluoride, and cyanoethylated polyvinyl alcohol.

[0010] The base film includes a commercial PP single-layer film, a PE single-layer film, or a PP and PE multi-layer composite base film, with a thickness of 5-12 μm and a porosity of 30-70%.

[0011] The composite diaphragm of the present invention is provided with a ceramic coating and an organic polymer coating, and the organic polymer coating is prepared by an electrostatic spinning process to form a porous structure, which significantly improves the wettability and liquid retention rate of the electrolyte. Through process adjustment, a spherical bead structure is formed, and due to the introduction of the beads, the prepared composite diaphragm exhibits stable superhydrophobic properties and significantly reduces the moisture content of the diaphragm. In addition, the spherical beads are used as a fulcrum to increase the contact area with the pole piece during hot pressing, significantly improving the adhesion between the diaphragm and the pole piece, thereby improving the safety performance and stability of the lithium ion battery during use.

[0012] The present invention also provides a method for preparing a composite diaphragm, comprising the following steps: 1) The ceramic coating is obtained by coating and drying a ceramic coating liquid on one or both sides of the base film; 2) The organic polymer coating is obtained by spinning, hot pressing and drying an organic polymer spinning solution on the surface of the ceramic coating.

[0013] Preferably, the ceramic coating liquid comprises the following raw materials in parts by weight: 25-45 parts of ceramic particles, 0.5-4 parts of wetting agent, 5-10 parts of binder, and 60-100 parts of deionized water.

[0014] Further preferably, the ceramic particles are one or more combinations of alumina, boehmite, boron nitride, silica, titanium oxide, zirconium oxide, and zeolite particles, and the particle size distribution is 0.3-1µm, preferably 0.5-0.8µm; the wetting agent is one or more combinations of polyether-modified siloxane, sodium polyacrylate, and succinic acid; the binder is one or more combinations of polyacrylate, polyvinyl alcohol, polymethyl methacrylate, and epoxy resin.

[0015] Preferably, the organic polymer spinning solution comprises the following raw materials in parts by weight: 5-20 parts of organic polymer and 80-95 parts of organic solvent; the organic solvent comprises one or more of DMAC, DMF and DMSO.

[0016] The present invention uses a polyolefin porous membrane as a base membrane, coats a ceramic coating on the surface of the polyolefin porous membrane, and then prepares an organic polymer coating on the ceramic coating. The ceramic coating is located between the polyolefin porous membrane and the organic polymer coating, which can ensure the thermal shrinkage performance of the separator. At the same time, the risk of the ceramic layer falling off is reduced, and the adhesion with the pole piece is improved.

[0017] The present invention also provides a detailed preparation method of the composite diaphragm, comprising the following steps: 1) Preparation of ceramic coating: Ceramic particles, wetting agent, binder and deionized water are mixed to obtain ceramic coating liquid under certain conditions, which is coated on the base film by micro-concave coating method and dried at 45-65°C for 1 min to obtain the ceramic coating.

[0018] 2) Preparation of organic polymer coating: The organic polymer is dissolved in an organic solvent to prepare an organic polymer spinning solution. The spinning solution is added to a syringe and spun under certain voltage, extrusion speed and receiving distance conditions. The receiver end is a ceramic coated base film. The composite membrane is collected and hot-pressed at 80~120℃ and 5~15 MPa for 3~15min to obtain the final composite diaphragm.

[0019] Preferably, in step 1), the ceramic coating liquid is prepared under the following conditions: stirring at room temperature and 1300-2000 rpm / min for 30-120 min.

[0020] Preferably, in the step 2), the spinning conditions are: voltage 15-30 kV, extrusion speed 1.5-3 ml / h, receiving distance 8-25 cm.

[0021] The present invention also provides application of the composite diaphragm, which is applied to lithium ion batteries.

[0022] The organic polymer coating contains a large number of beaded structures and exhibits stable superhydrophobic properties.

[0023] The ceramic coating is prepared by a water-based coating process, which can improve the heat resistance of the diaphragm and the wettability of the electrolyte. The organic polymer coating is prepared by electrospinning, and a spherical beaded structure is formed by adjusting the spinning parameters. Because it contains a large number of beaded structures, the prepared composite diaphragm exhibits stable super-hydrophobic properties. In addition, the organic polymer has extremely high heat resistance and adhesion to the electrode, and the electrospinning preparation process gives the diaphragm an extremely high porosity. The composite diaphragm of the present invention has a thin thickness, low resistance, and high temperature resistance; it has excellent thermal stability and mechanical properties. Not only that, it also has extremely high electrolyte wettability and liquid retention rate, and significantly reduces the moisture content of the diaphragm. The assembled lithium-ion battery has the characteristics of excellent cycle performance and high safety performance.

[0024] Compared with the prior art, the present invention has the following advantages: 1. The composite diaphragm of the present invention innovatively sets an electrospun spherical beaded structure organic polymer coating. The organic polymer coating is prepared by an electrospinning process to form a porous structure, which significantly improves the wettability and liquid retention rate of the electrolyte. Through process adjustment, a spherical beaded structure is formed. Due to the introduction of the beads, the prepared composite diaphragm exhibits stable superhydrophobic properties and significantly reduces the moisture content of the diaphragm. And using the spherical beads as a fulcrum, the contact area with the pole piece is increased during hot pressing, which significantly improves the adhesion between the diaphragm and the pole piece, thereby improving the safety performance and stability of the lithium-ion battery during use.

[0025] 2. The ceramic coating and organic polymer coating described in the present invention can synergistically enhance the heat resistance of the diaphragm. Moreover, since the organic polymer coating is more tightly bonded to the electrode, the ceramic particles are not easy to fall off, which significantly improves the safety performance of the battery.

[0026] 3. The composite diaphragm has both the good heat resistance and mechanical properties of the ceramic coating, and the good electrolyte wettability and liquid retention rate of the electrospun organic polymer coating, while taking into account the effect of reducing the moisture content of the diaphragm and improving the adhesion between the diaphragm and the pole piece. It is beneficial to improve the stability of the diaphragm during high-rate charge and discharge and the rate performance of the battery. Due to the hardness of the ceramic particles, it plays a role in hindering the growth of dendrites and avoiding perforation and damage of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a surface morphology diagram of the composite diaphragm in Example 1 of the present invention.

[0028] Figure 2 It is a surface morphology picture of the composite diaphragm in comparative example 1 of the present invention.

[0029] Figure 3 It is a battery performance diagram of the composite diaphragm in Examples 1-2 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0030] The present application is described in detail below in conjunction with embodiments, but the present application is not limited to the following embodiments.

[0031] Example 1

[0032] The composite membrane is prepared, comprising the following steps 1) Preparation of ceramic coating (by weight): 30 parts of alumina (particle size distribution 0.3-1µm), 2 parts of polyether modified siloxane (Guangdong Shierli New Materials Co., Ltd., product model: BESM®2411), 6 parts of polyacrylate (Jinan Feiyue Chemical Co., Ltd.), and 85 parts of deionized water were mixed, stirred at room temperature and 1500rpm / min for 90min to obtain a ceramic coating liquid, coated on the base film by micro-concave coating, and dried at 55℃ for 1min to obtain a ceramic coating.

[0033] 2) Preparation of organic polymer coating (by weight): 10 parts of cyanoethylated polyvinyl alcohol (Wuxi Sanyou New Material Technology Co., Ltd.) were dissolved in 90 parts of DMAC to prepare an organic polymer spinning solution. The spinning solution was added to a syringe and electrospun at a voltage of 22 kV, an extrusion speed of 1.5 ml / h, and a receiving distance of 12 cm. The receiving end was the ceramic coating surface of the ceramic coated base film. The composite membrane was collected and hot pressed at 85 ° C and 8 MPa for 5 min to obtain the final composite diaphragm.

[0034] The base film is a single-layer PE base film with a thickness of 5µm and a porosity of 55%. The thickness of the ceramic coating is 2µm, and the thickness of the organic polymer coating is 3µm.

[0035] Example 2

[0036] 1) Preparation of ceramic coating: 30 parts of alumina (particle size distribution 0.3-1µm), 2 parts of polyether modified siloxane (Guangdong Shierli New Materials Co., Ltd., product model: BESM®2411), 6 parts of polyacrylate (Jinan Feiyue Chemical Co., Ltd.), and 85 parts of deionized water were mixed, stirred at room temperature and 1500rpm / min for 90min to obtain a ceramic coating liquid, coated on the base film by micro-concave coating, and dried at 55℃ for 1min to obtain a ceramic coating.

[0037] 2) Preparation of organic polymer coating: 8 parts of cyanoethylated polyvinyl alcohol (Wuxi Sanyou New Material Technology Co., Ltd.) and 2 parts of polyvinylidene fluoride (USA Solvay PVDF5130) were dissolved in 90 parts of DMAC to prepare an organic polymer spinning solution. The spinning solution was added to a syringe and electrospun at a voltage of 24 kV, an extrusion speed of 1.3 ml / h, and a receiving distance of 18 cm. The receiver end was a ceramic coated base film. The composite membrane was collected and hot pressed at 95 ° C and 10 MPa for 3 min to obtain the final composite diaphragm.

[0038] The base film is a 5µm single-layer PE base film with a porosity of 55%. The thickness of the ceramic coating is 2µm and the thickness of the organic polymer coating is 3µm.

[0039] Example 3

[0040] The composite membrane is prepared, comprising the following steps 1) Preparation of ceramic coating (by weight): 25 parts of boehmite (particle size distribution 0.3-1µm), 4 parts of succinic acid (Jinan Lebin Chemical Co., Ltd.), 5 parts of polymethyl methacrylate (Dongguan Zhengtao Plastic Co., Ltd.), and 60 parts of deionized water were mixed, stirred at room temperature and 1300 rpm / min for 120 min to obtain a ceramic coating liquid, coated on the base film by micro-concave coating, and dried at 45°C for 1 min to obtain a ceramic coating.

[0041] 2) Preparation of organic polymer coating (by weight): 5 parts of polyacrylonitrile (Pande International Trading Co., Ltd.) were dissolved in 95 parts of DMF to prepare an organic polymer spinning solution. The spinning solution was added to a syringe and electrospun at a voltage of 30 kV, an extrusion speed of 2 ml / h, and a receiving distance of 25 cm. The receiving end was the ceramic coating surface of the ceramic coated base membrane. The composite membrane was collected and hot pressed at 120°C and 15 MPa for 3 minutes to obtain the final composite diaphragm.

[0042] The base film is a 12µm thick PP and PE multilayer composite base film with a porosity of 30%. The ceramic coating is 1µm thick and the organic polymer coating is 0.3µm thick.

[0043] Example 4

[0044] 1) Preparation of ceramic coating: 30 parts of silicon dioxide (particle size distribution 0.3-1µm), 15 parts of zirconium oxide (particle size distribution 0.3-1µm), 0.5 parts of sodium polyacrylate (Shandong Wanhua Tianhe New Materials Co., Ltd.), 10 parts of polyvinyl alcohol (Hebei Wanshan New Materials Technology Co., Ltd.), and 100 parts of deionized water were mixed, stirred at room temperature and 2000rpm / min for 30min to obtain a ceramic coating liquid, coated on the base film by micro-concave coating, and dried at 65℃ for 1min to obtain a ceramic coating.

[0045] 2) Preparation of organic polymer coating: 20 parts of polyaryletherketone (AvaSpire AV-651 GF30, Solvay, USA) were dissolved in 80 parts of DMSO to prepare an organic polymer spinning solution. The spinning solution was added to a syringe and electrospun at a voltage of 15 kV, an extrusion speed of 3 ml / h, and a receiving distance of 8 cm. The receiving end was a ceramic-coated base film. The composite membrane was collected and hot-pressed at 80 ° C and 5 MPa for 15 min to obtain the final composite diaphragm.

[0046] The base film is a 7µm single-layer PP base film with a porosity of 70%. The thickness of the ceramic coating is 3µm and the thickness of the organic polymer coating is 5µm.

[0047] Comparative Example 1 The composite membrane is prepared, comprising the following steps 1) Preparation of ceramic coating: 30 parts of alumina, 2 parts of polyether-modified siloxane, 6 parts of polyacrylate, and 85 parts of deionized water were mixed, stirred at room temperature and 1500 rpm / min for 90 min to obtain a ceramic coating liquid, coated on the base film by micro-concave coating, and dried at 55°C for 1 min to obtain the final composite diaphragm.

[0048] The base film is a 5µm single-layer PE base film with a porosity of 55%. The thickness of the ceramic coating is 2µm.

[0049] Comparative Example 2 The 5µm single-layer PE base membrane used in the above-mentioned Example 1 has a porosity of 55%.

[0050] Performance Test 1: The diaphragms obtained in Examples 1-2 and Comparative Examples 1-2 were tested for heat shrinkage and electrolyte wettability, respectively. The specific test methods are as follows. The test results are shown in Table 1.

[0051] Thermal shrinkage rate: Cut the diaphragm into film samples with length × width = 100 × 100 mm, measure its longitudinal and transverse lengths, put them into a vacuum oven and bake them for 1 hour respectively, take out the diaphragm samples, cool them to room temperature, measure their longitudinal and transverse lengths again, calculate the thermal shrinkage rate, and characterize the heat resistance of the diaphragm. Test them at three temperatures of 105℃, 120℃ and 150℃ respectively.

[0052] Electrolyte wettability: The electrolyte wettability uses electrolyte solvent (ethylene carbonate and dimethyl carbonate, with a mass ratio of 1:1) as the test object to observe the diffusion diameter of the electrolyte at different times.

[0053] Membrane moisture test: Use Shenzhen Laixi Te LXT-800 battery membrane moisture detector to test the membrane moisture.

[0054] Diaphragm tensile strength: The tensile strength of the composite diaphragm was tested using a universal testing machine, with reference to the national standard GB / T1040.3-2006.

[0055] Depend on Figure 1 and Figure 2 It can be seen that the organic polymer coating in Example 1 is a structure with many spherical shapes on a spinning line, and the ceramic coating in Comparative Example 1 has a dense ceramic coating structure.

[0056] As can be seen from Table 1, the heat resistance of the diaphragms provided by Examples 1 to 2 and Comparative Example 1 is much higher than that of Comparative Example 2, indicating that the introduction of the composite functional layer significantly increases the thermal stability of the diaphragm. As can be seen from Table 1, compared with the base membrane of Comparative Example 2, the electrolyte wettability and liquid absorption rate of the composite diaphragm provided by Examples 1 to 2 are significantly improved, and are also significantly higher than the ceramic coated diaphragm in Comparative Example 1, indicating that the spinning layer structure and composition can significantly improve the wettability of the diaphragm to the electrolyte. At the same time, due to the introduction of the beaded structure, the composite diaphragm provided by Examples 1 to 2 exhibits stable superhydrophobic properties, which significantly reduces the moisture content of the diaphragm compared with Comparative Examples 1 and 2. And the composite diaphragm provided by Examples 1 to 2 has a higher tensile strength, which indicates that it has better mechanical properties.

[0057] Depend on Figure 3It can be seen that the ceramic coated diaphragm in Comparative Example 1 has a slightly improved rate performance compared to the traditional PE-based membrane in Comparative Example 2 due to the improved wettability of the electrolyte. The composite diaphragms in Examples 1 and 2 have significantly improved rate performance due to the introduction of the organic polymer coating. This is due to the extremely high electrolyte wettability, hydrophobicity, and adhesion to the electrode sheet of the spherical bead spinning structure.

[0058] Table 1 shows the heat shrinkage, liquid absorption, membrane moisture test, electrolyte diffusion diameter and tensile strength of the composite diaphragm in Examples 1-2 of the present invention and Comparative Examples 1-2.

[0059]

[0060] In summary, the present invention provides a composite diaphragm and its application in a lithium-ion battery. The composite diaphragm includes a substrate and at least one ceramic coating and at least one organic polymer coating coated on the surface of the substrate. The thickness of the ceramic coating is 1-3µm, and the thickness of the organic polymer coating is 0.3-5µm. The ceramic coating is prepared by an aqueous coating process, which can improve the heat resistance and electrolyte wettability of the diaphragm. The organic polymer coating is prepared by electrospinning to form a spherical beaded structure. Because it contains a large number of beaded structures, the prepared composite diaphragm exhibits stable superhydrophobic properties. In addition, the organic polymer has extremely high heat resistance and adhesion to the electrode sheet, and the electrospinning preparation process gives the diaphragm an extremely high porosity. The composite diaphragm of the present invention is thin and resistant to high temperatures; it has excellent thermal stability and mechanical properties. In addition, it also has extremely high electrolyte wettability and liquid retention rate, and significantly reduces the moisture content of the diaphragm. The assembled lithium-ion battery has the characteristics of excellent cycle performance and high safety performance.

[0061] The above are only some embodiments of the invention, and do not limit the present invention in any form. All raw material ratios, upper and lower limits of working conditions and interval values ​​in the preparation process of the present invention can realize the present invention, and the embodiments are not listed one by one here. Any person familiar with this profession, without departing from the technical solution of the present invention, when using the above technical content to make some changes or modifications to an equivalent embodiment of decorating, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still belongs to the scope of the technical solution of the present invention.

Claims

1. A composite diaphragm, characterized in that: The composite diaphragm comprises a base film, one or more ceramic coating layers attached to one or two surfaces of the base film, and one or more organic polymer coating layers attached to the surface of the ceramic coating layer; The thickness of ceramic coating is 1-3µm, and the thickness of organic polymer coating is 0.3-5µm; The organic polymer is one or more of aramid, polyimide, polyaryletherketone, polyacrylonitrile, polyvinylidene fluoride, and cyanoethylated polyvinyl alcohol; The base film includes a commercial PP single-layer film, a PE single-layer film, and a PP and PE multi-layer composite base film, with a thickness of 5-12µm and a porosity of 30-70%.

2. A method for preparing the composite diaphragm according to claim 1, characterized in that: The steps include: 1) The ceramic coating is obtained by coating and drying a ceramic coating liquid on one or both sides of the base film; 2) The organic polymer coating is obtained by spinning, hot pressing and drying an organic polymer spinning solution on the surface of the ceramic coating.

3. The method for preparing the composite diaphragm according to claim 2, characterized in that: The ceramic coating liquid is composed of the following materials in parts by weight: 25-45 parts of ceramic particles, 0.5-4 parts of wetting agent, 5-10 parts of binder, and 60-100 parts of deionized water; The ceramic particles are one or a combination of two or more of alumina, boehmite, boron nitride, silicon dioxide, titanium oxide, zirconium oxide, and zeolite particles, and the particle size distribution is 0.3-1µm; The wetting agent is one or a combination of two or more of polyether-modified siloxane, sodium polyacrylate, and succinic acid; The binder is one of polyacrylate, polyvinyl alcohol, polymethyl methacrylate and epoxy resin, or a combination of two or more thereof.

4. The method for preparing the composite diaphragm according to claim 2, characterized in that: The organic polymer spinning solution comprises the following raw materials in parts by weight: 5-20 parts of organic polymer and 80-95 parts of organic solvent; the organic solvent comprises one or more of DMAC, DMF and DMSO.

5. The method for preparing the composite diaphragm according to claim 2, characterized in that: The steps include: 1) Preparation of ceramic coating: ceramic particles, wetting agent, binder and deionized water are mixed, stirred at room temperature and 1300-2000 rpm / min for 30-120 min to obtain a ceramic coating liquid, coated on the base film by micro-concave coating, and dried at 45-65°C for 1-5 min to obtain a ceramic coated base film with a ceramic coating; 2) Preparation of organic polymer coating: dissolving an organic polymer in an organic solvent to prepare an organic polymer spinning solution; adding the spinning solution into a syringe, and electrospinning at a voltage of 15-30 kV, an extrusion speed of 1.5-3 ml / h, and a receiving distance of 8-25 cm; the surface material of the receiver end is a ceramic coating of a ceramic-coated base film; The composite membrane is collected and hot-pressed at 80-120° C. and 5-15 MPa for 3-15 min to obtain a final composite diaphragm.

6. An application of the composite diaphragm according to claim 1, characterized in that: The composite diaphragm can be used as a diaphragm in lithium ion batteries.

Citation Information

Patent Citations

  • Composite lithium ion battery ceramic diaphragm and preparation method thereof

    CN104681764A

  • Lithium battery diaphragm with high thermostability and preparation method thereof

    CN109411682A

  • Method for modifying lithium battery diaphragm by temperature-resistant macromolecules and corresponding lithium battery diaphragm

    CN111129396A

  • Preparation method of high-safety long-life ceramic diaphragm

    CN113224458A

  • Polyimide coating modified polyolefin composite diaphragm and preparation method thereof

    CN113969006A

Cited By

  • Ultrathin organic-inorganic composite diaphragm for alkaline water electrolyser as well as preparation method and application of ultrathin organic-inorganic composite diaphragm

    CN120060921A

  • Composite diaphragm, preparation method thereof and battery

    CN121054955A